2022
DOI: 10.3390/jcm11072060
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Navigation in Mandibular Reconstruction: Accuracy Evaluation of an Innovative Protocol

Abstract: Aim: the purpose of this work is to present an innovative protocol for virtual planning and surgical navigation in post-oncological mandibular reconstruction through fibula free flap. In order to analyze its applicability, an evaluation of accuracy for the surgical protocol has been performed. Methods: 21 patients surgically treated for mandibular neoplasm have been included in the analysis. The Brainlab Vector Vision 3.0® software for surgical navigation has been used for preoperative surgical planning and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…All the procedures were successfully performed, with no reported complications among the patients. Navigation accuracy measured was: <0.5 mm in 40.47% (17) of cases, <1 mm in 45.23% (19) of cases and <1.5 mm in 14.28% (6) of cases. The recorded mean accuracy was < 0.87 mm, with a standard deviation of 0.5 mm.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…All the procedures were successfully performed, with no reported complications among the patients. Navigation accuracy measured was: <0.5 mm in 40.47% (17) of cases, <1 mm in 45.23% (19) of cases and <1.5 mm in 14.28% (6) of cases. The recorded mean accuracy was < 0.87 mm, with a standard deviation of 0.5 mm.…”
Section: Resultsmentioning
confidence: 89%
“…Hirch et al ( 2009) and observed that real-time guidance offered by surgical navigation in mandibular reconstruction with vascularized fibula flap reduces the margin of error compared to free-hand techniques, decreases surgery duration, and demonstrates high accuracy and applicability [14][15][16]. Sozzi et al (2022) describe in their protocol how the positions of the screw holes for the reconstruction plate are prerecorded on a 3D model of the patient's jaw. Subsequently, before performing the resection, the screw holes are realized using a recorded drill, whose bit position can be tracked in real-time on CT images to ensure precise placement of the screws as per the planned location.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical DNS in mandibular reconstruction is considered challenging for practitioners because of the constant mandibular movement that affects precise synchronization of the data set with the navigation system. Sozzi et al (2022) created a dental splint using radiopaque fiducial marker points for surgical navigation. The position between the splint and mandible remained unchanged during the phases of computed tomography (CT) image acquisition and surgery, ensuring a precise match between the patient and radiological data.…”
Section: Dns In Oral and Maxillofacial Surgerymentioning
confidence: 99%
“…Postoperative imaging and examination showed that the new mandible was well positioned with good occlusion in all cases, and facial symmetry was achieved in all cases with an unrestricted opening. Sozzi et al (2022) proposed an innovative protocol for virtual planning and surgical navigation in post-oncological mandibular reconstruction through a bula free ap and evaluated the accuracy of the surgical protocol. The location of mandibular markers was evaluated for postoperative accuracy in the preoperative and postoperative CT scans of 21 patients who underwent surgical treatment for mandibular tumors.…”
Section: Trauma and Facial Reconstructionmentioning
confidence: 99%